EFEKTIVITAS PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 TERHADAP MOTIVASI BELAJAR MAHASISWA TEKNIK ELEKTROMEDIS STIKES MUHAMMADIYAH ACEH - Wirda Wirda; Hayati Hayati; Ani Darliani; Erli Mauvizar (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Education is also a process in forming basic abilities both in the form of intelligent thinking and emotional feelings that are directed to human nature and to each other. Higher education institutions are required to be able to organize online learning. Online learning makes students free or a lot of time and can study anywhere. In addition, students can also get in touch with their lecturers through the use of several applications such as Google Classroom, Zoom, Google Meet, Video Conference or via the Whatsapp Group. The application of online learning is one of the learning innovations from the industrial revolution 4.0 and educators and students are expected to be able to adapt and take advantage of advances in technology and information. However, during the implementation of online learning there are obstacles in terms of aspects of facilities and infrastructure and human resources. Limited network connectivity, the high need for internet quota which is a serious obstacle for low-income people, and the lack of skills in using information technology faced by lecturers. Based on the results of the study of 52 respondents, the score of the online learning variable is included in the high category or percentage, so it becomes 65% if it is interpreted as being in the range of values 61% - 80% with the effective category. So that the results of the percentage test show that overall in each indicator online learning is categorized as effective with an average result of 65%.